Assessment of Psoas Muscle Index in Middle-Aged Type 2 Diabetes Patients: Impact of Insulin Therapy on Sarcopenia - Taskent, Ismail; Ece, Bunyamin; Aydin, Sonay (MDPI AG, 2024)
Objective: Sarcopenia, characterized by progressive skeletal muscle loss, poses significant health risks, including physical impairment and mortality. The relationship between sarcopenia and insulin resistance suggests insulin therapy’s potential in preserving muscle mass, particularly in Type 2 diabetes mellitus (T2DM) patients. This study aims to evaluate the Psoas Muscle Index (PMI) via computed tomography (CT) in middle-aged T2DM patients on insulin therapy versus oral antidiabetic drugs (OAD) and controls. Methods: This retrospective study included 107 middle-aged T2DM patients undergoing non-contrast CT scans and 58 age-matched controls. CT images were analyzed to calculate PMI. Statistical analysis included Chi-square tests, independent samples t-tests, Mann–Whitney U tests, and correlation analyses. Results: Insulin-treated patients exhibited higher PMI than OAD users (p < 0.001), while OAD users had lower PMI than controls (p < 0.001). No significant difference was found between insulin-treated patients and controls (p = 0.616). Negative correlations were observed between T2DM duration/age and PMI across all groups, with a positive correlation between T2DM duration and BMI observed in the OAD group. Conclusions: Insulin therapy in T2DM patients, regardless of age or disease duration, positively impacts muscle mass, highlighting its potential in preserving muscular health and advocating for tailored treatment strategies in T2DM management.
Keywords: Male; insulin; Sarcopenia; type 2 diabetes mellitus; psoas muscle density; Computer applications to medicine. Medical informatics; psoas muscle index; R858-859.7; computed tomography; Middle Aged; Article; sarcopenia; Diabetes Mellitus, Type 2; Case-Control Studies; Humans; Insulin; Hypoglycemic Agents; Female; Tomography, X-Ray Computed; Psoas Muscles; Retrospective Studies; Aged; 3. Good health